Data analysis for database design - Howe, D. R. (David R.) (Oxford ; Boston : Butterworth Heinemann, 2001)
Data analysis for database design is a subject of great practical value to systems analysts and designers. This classic text has been updated to include chapters on distributed database systems, query optimisation and object-orientation. The SQL content now includes features of SQL92 and SQL 99. With new databases coming online all the time and the general expansion of the information age, it is increasingly important to ensure that the analysis and model of a database design is accurate and robust. This is an ideal book for helping you to ensure that your database is well designed and therefore user friendly. Increased material on SQL including the latest developments Practical approach to explaining techniques and concepts Contains many questions and answer pointers.
Database systems -- Database management system architecture -- Tables -- Redundant vs duplicated data -- Repeating groups -- Determinants and identifiers -- Fully-normalised tables -- Introduction to entity-relationship modelling -- Properties of relationships -- Decomposition of many-many relationships -- Connection traps -- Skeleton entity-relationship models -- Attribute assignment -- First-level design -- Second-level design -- Distributed database systems -- Relational algebra -- Query optimisation -- The SQL language -- Object-orientation.
Includes bibliographical references (p. [317]-318) and index.
Keywords: Database design; System analysis; Electronic books